Transformational Leadership and Job Satisfaction in the Banking Sector: A Review - Belias, Dimitrios; Koustelios, Athanasios (International Review of Management and Marketing, 2014)
The purpose of the present study is to provide a critical review of the relation between transformational leadership and the levels of job satisfaction experienced by bank employees. An organization’s or institution’s leadership refers to its leader’s style of providing direction, implementing plans and motivating employees. Transformational leadership is a specific leadership style applied by superiors who motivate their subordinates to perform at a higher level by inspiring them, offering them intellectual challenges and paying attention to their individual needs. Job satisfaction refers to the employees’ perceptions of their working environment, relations among colleagues, earnings and promotion opportunities. The review shows that contemporary job-related phenomena like job satisfaction are related to employees’ relations with colleagues and superiors, performance and perceptions of their organization’s specific culture. In addition, the employees’ preference of leadership style is likely to be affected by several factors, including demographic characteristics. Therefore, the reciprocal relation between organizational culture and transformational leadership in job satisfaction in the banking field is revealed in the review, and several conclusions and suggestions are formed. Keywords: Organizational Culture; Transformational Leadership; Leadership Style; Job Satisfaction; Banking sector JEL Classifications: J24; M11; M12; M14; O15